Using Jigsaw Strategies to Improve Participation and English Speaking Skills - Y. Kiuk; I. G. W. Suputra; L. D. S. Adnyani (Universitas Pendidikan Ganesha, 2021)
There are still many teachers who do not apply appropriate learning strategies for students. This has an impact on the students' lack of English speaking ability. The purpose of implementing this Lesson Study is to increase the level of student participation in learning English. The Lesson Study is carried out in three stages in its implementation, namely Plan, Do, and SEE. In the Plan stage, the author and the Lesson Study team plan the implementation of the Lesson Study by determining the implementation time, materials, classes, and strategies used. The population in this study amounted to 30 students. In practice, data collection is done through observation, interviews, and lesson study techniques carried out in teams. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The study results are the use of the Jigsaw strategy in learning due to the lack of student participation and the willingness of students to speak in English in learning English. After the implementation of the Jigsaw strategy, the students became more active. The result of this reflection (see) stage is that the implementation of the Jigsaw strategy has been successful, and for media problems such as LCD and classroom management by model teachers need to be improved again. Seeing the success of this strategy, the authors suggest that teachers use the Jigsaw strategy as a cooperative learning strategy that will help students become more active.